The Influence Of Social Media, Peer Support, And The Trade War On Entrepreneurial Interest Among Final-Semester Management Students At Universitas Pembangunan Panca Budi Medan - Ratna Sari Hasibuan; Wulan Dayu; Dian Septiana Sari (Jurnal Fokus Manajemen, 2026)
This study analyzes the influence of social media, peer support, and the trade war on entrepreneurial interest among final-year Management students at Universitas Pembangunan Panca Budi Medan. Using a quantitative associative design, data were collected through a Likert-scale questionnaire from 92 respondents selected by the Slovin formula from 514 students. Data analysis employed validity and reliability testing, multiple linear regression, t-test, F-test, and determination coefficient using SPSS version 25. The results show that social media, peer support, and the trade war positively and significantly affect entrepreneurial interest, with social media having the most dominant influence. Simultaneously, the three variables explain 72.4% of the variance in students’ entrepreneurial interest. These findings highlight the importance of digital engagement and social interaction in fostering entrepreneurial intentions among students amid global economic uncertainty.